Management and utilization of acid sulfate soils for aquaculture : - Singh, Virendra P. (Submitted to FAO/UNDP Regional, 1985)
Contents: Acid sulfate soils, formation of acid sulfate soils, production of acidity, soil survey, soil analysis and evaluation of data...